CONTROLLED RELEASE FERTILIZER IN THE GROWTH OF Moringa oleifera LAM. SEEDLINGS - Rosa, Thuanny Lins Monteiro; Jordaim, Renan Baptista; Alexandre, Rodrigo Sobreira; Araujo, Caroline Palacio de; Gonçalves, Fabrício Gomes; Lopes, José Carlos (Floresta, 2018)
Moringa oleifera presents important medicinal properties, and its seeds are used to treat water for human consumption and wastewater. The aim of the present study was to analyze the initial growth of M. oleifera seedlings in enriched commercial substrate with differing doses of controlled release fertilizer. The experimental was designed in randomized blocks, with four repetitions of 16 seedlings each. The treatment used doses of controlled release fertilizer, with 0; 2; 4; 6; and 8 kg m-3 of commercial substrate. A hundred days after installing the experiment, the following characteristics were analyzed: height of the aerial part; diameter of the root collar; length; volume; and dry mass of the roots and aerial part. Additionally, the relation between the height of the aerial part and the diameter of the root collar and the Dickson quality index (DQI) were determined. The data was submitted to analysis of variance and to the Shapiro-Wilk test to verify the normality and regression. Controlled release fertilizer at a dose of 5.37 kg m-3 of substrate is recommended for M. oleifera seedling production.